Marital power, spousal relationship, and intergenerational support - Dandan Zheng; Jinhua Di (The Journal of Chinese Sociology, 2018)
Abstract This paper explores the effect of marital power distribution and the spousal relationship on family intergenerational support to older parents using CGSS2006 data. The findings include the following: (1) the more power the wife has, the less economic support the family probably gives to the paternal parents; (2) the spousal relationship contributes to both paternal and maternal intergenerational economic support to older parents; and (3) the spousal relationship can mediate the effect of marital power distribution on paternal economic support. The better relationship the couple has, the less marital power affects economic support to the paternal parents. The mechanism of maternal support requires further exploration.